2019
DOI: 10.1080/14756366.2019.1666836
|View full text |Cite
|
Sign up to set email alerts
|

Novel 2-substituted-benzimidazole-6-sulfonamides as carbonic anhydrase inhibitors: synthesis, biological evaluation against isoforms I, II, IX and XII and molecular docking studies

Abstract: Inhibition of Carbonic Anhydrases (CAs) has been clinically exploited for many decades for a variety of therapeutic applications. Within a research project aimed at developing novel classes of CA inhibitors (CAIs) with a proper selectivity for certain isoforms, a series of derivatives featuring the 2-substituted-benzimidazole-6-sulfonamide scaffold, conceived as frozen analogs of Schiff bases and secondary amines previously reported in the literature as CAIs, were investigated. Enzyme inhibition assays on phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 41 publications
1
31
0
Order By: Relevance
“…Using the data filed in the Protein Data Bank ( https://www.rcsb.org/ ) database, the structure of the COVID-19 virus main protease (M pro ) was obtained, identified in the repository as The crystal structure of COVID-19 main protease in complex with an inhibitor N3 PDB ID: 6LU7 , composed of three domains, domain I (residue 8–101), domain II (102–184), domain III (201–303), and a long loop (185–200) binding domain II to domain III; its structure was filed in the Protein Data Bank with a resolution of 2.16 Å, determined from X-ray diffraction, classified as viral protein, Bat SARS-like coronavirus organism, and Escherichia coli BL21(DE3) expression system [ 6 ]. In the process of preparing the SARS-CoV-2 main protease, all residues were removed and polar hydrogens were added [ 7 , 8 ], producing favorable protonation states for molecular docking [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the data filed in the Protein Data Bank ( https://www.rcsb.org/ ) database, the structure of the COVID-19 virus main protease (M pro ) was obtained, identified in the repository as The crystal structure of COVID-19 main protease in complex with an inhibitor N3 PDB ID: 6LU7 , composed of three domains, domain I (residue 8–101), domain II (102–184), domain III (201–303), and a long loop (185–200) binding domain II to domain III; its structure was filed in the Protein Data Bank with a resolution of 2.16 Å, determined from X-ray diffraction, classified as viral protein, Bat SARS-like coronavirus organism, and Escherichia coli BL21(DE3) expression system [ 6 ]. In the process of preparing the SARS-CoV-2 main protease, all residues were removed and polar hydrogens were added [ 7 , 8 ], producing favorable protonation states for molecular docking [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, drug repositioning has been a strategy adopted by several researchers to seek effective treatment in a short period. Besides that, a virtual screening based on molecular docking emerges as an important tool for obtaining new antiviral molecules, where researchers can use this tool as a complementary approach so that the synthesis of new compounds or the repositioning of drugs can be assigned [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To rationalise the SAR data attained for various substitutions of newly designed secondary sulphonamides ( Table 1 ), a series of molecular modelling studies were performed on compounds 3 and 5 , as they are the most potent inhibitors of hCA IX as well as the most selective over the other tested hCAs (I, II, and IV) of the whole set. In this process, the AutoDock4 Zn docking protocol, devised for docking experiments on zinc-chelating ligands, was employed as implemented in our previous reports on hCAIs 15 , 37 . The best docking solution, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Another potent compound (17) also exhibited good inhibition at low μM range against hCA IX and XII, with an inhibitory constant (K i ) value of 5.9 and 7.9 μM respectively. Hence, it is concluded that these benzimidazole derivatives might be potential anticancer agents exhibiting a novel mechanism through inhibition of hCA isoforms IX and XII [46]. Asta Zubriene et al have reported a series of novel benzenesulfonamides with benzimidazole derivatives as selective human carbonic anhydrase I, II, VII, XII, and XIII inhibitors.…”
Section: Carbonic Anhydrase Inhibitorsmentioning
confidence: 99%